An example of facade colour design of mass housing - Ünver, R; Öztürk, LD (JOHN WILEY & SONS INC, 2002)
The colours and architectural characteristics of building facades are the major factors affecting the general appearance of cities. When cities are examined from various perspectives, first impressions are obtained from the geometrical forms and facade colours of buildings. The facade colour arrangements should reflect the features of the region and buildings. In this context various features of natural and artificial environments such as plant life, water elements, climate, and historical texture should be examined, and a facade colour arrangement should be designed according to the examination results. In addition, the other factors effective in determining the colour and style of a building, such as social-cultural background of the society and traditional and natural building materials, should not be forgotten because in some regions traditional buildings with special construction styles, materials, and colours create a specific identity for the settlements and cities. The aims of this article are to elucidate the colour contrast, colour arrangement, and colour design stages of mass housing and to explain the colour design of Bizimkent Mass Housing, which was constructed in a new dwelling zone in Istanbul, Turkey, as an example of such an arrangement. (C) 2002 Wiley Periodicals, Inc.
Keywords: architecture; city planning; colour arrangement; facade colour; mass housing; Chemistry; Optics; Imaging Science & Photographic Technology